FUNDAMENTALS OF PROFESSIONALISM DEVELOPMENT ON THE EXAMPLE OF PRACTICAL EXERCISES ON FORMING THE SKILLS AND SKILLS OF FUTURE TEACHERS - Sharipova Gozal Sadikovna , Barchinoy Kurbonova , Nazokat Akhmedova , Sevarakhon Sulaymanova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The most important psychological characteristics for women entrepreneurs are: high communication skills and courage in establishing social ties; leadership, emotional stability; practical direction of thinking; a tendency to combine tradition with novelty, to take risks. This article describes the competencies of entrepreneurship and pedagogical and psychological aspects of their development in female students of higher education institutions of the republic.